Long‐acting antipsychotic medication as first‐line treatment of first‐episode psychosis with comorbid substance use disorder. Issue 1 (24th May 2019) - Abdel‐Baki, Amal; Thibault, Dominic; Medrano, Sofia; Stip, Emmanuel; Ladouceur, Martin; Tahir, Ramzan; Potvin, Stephane
Abstract: Aim: Substance use disorder (SUD) is highly prevalent among patients with first‐episode psychosis (FEP) and associated with poor adherence and worst treatment outcomes. Although relapses are frequent in FEP, current literature on long‐acting injectable antipsychotics (LAI‐AP) use in FEP is scarce and studies often exclude patients with SUD. Objectives: To determine the impact of LAI‐AP as first‐line treatment on psychotic relapses or rehospitalizations in FEP patients with comorbid SUD (FEP‐SUD). Methods: This is a naturalistic, longitudinal, 3‐year prospective and retrospective study on 237 FEP‐SUD admitted in two EIS in Montreal, between 2005 and 2012. The patients were divided on the basis of first‐line medication introduced, either oral antipsychotics (OAP, n = 206) or LAI‐AP (n = 31). Baseline characteristics were compared using χ² test and analysis of variance, and Kaplan‐Meier survival analysis was performed on relapse and rehospitalization. Results: Compared to the OAP group, patients in the LAI‐AP group presented worse prognostic factors (eg, history of homelessness). Despite this, the LAI‐AP group presented a lower relapse rate (67.7% vs 76.7%), higher relapse‐free survival time (694 vs 447 days, P = 0.008 in Kaplan‐Meier analysis), and trends for reduced rehospitalization rates (48.4% vs 57.3%) and hospitalization‐free survival time (813 vs 619 days, P = 0.065 Kaplan‐Meier analysis). Of those receiving OAP as first‐line, 41.3% were eventually switched to LAI‐AP and displayed worst outcome in relapse and rehospitalization. Conclusion: LAI‐AP should be strongly considered as first‐line treatment of FEP‐SUD patients since this pharmacological option reduces the risk of relapse and rehospitalization even in the individuals with poor prognostic factors.